PENGGUNAAN GAME EDUKASI UNTUK MENINGKATKAN HAPALAN ANGKA DI TK DIPONEGORO SURABAYA - Muchamad Arif; Ida Ayu Puspita Sari; Lukman Junaedi; Rofik Jalal Rosyanafi (Universitas Narotama, 2020)
This study aimed to determine the use of educational games to improve memorization of 1-20 numbers in TK Diponegoro Surabaya. This school is located at Jalan Kedung Sroko No.17 Surabaya. The sample of this study was the children of B group Diponegoro Kindergarten. The authors used descriptive qualitative methods. The author focused on how to apply the use of educational games to improve memorization numbers 1-20 at Tk Diponegoro Surabaya. The author made observations during the 3x meeting. Each meeting, they play a different educational game but with the same content. The subject of the research was Diponegoro Kindergarten with 20 students. The results showed that students were very enthusiastic in learning to memorize numbers 1-20 as well as improving children's fine motor skills.. Keywords: educational games, memorizing, numbers 1-20